An Interactive Content Media on Information System iLearning+ - Untung Rahardja; Indri Handayani; Ninda Lutfiani; Fitra Putri Oganda (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Along with the increasing development of Information and Communication Technology (ICT), there has been a change in the learning approach method. Methods of face-to-face learning (conventional) and classrooms as implementation have now changed. The ilearning method approach has turned into the direction of future learning or as a learning age of knowledge. In the world of education, information becomes a vital need to support teaching and learning activities. In the online learning system that applied to iLearning+ information needs become critical needs therein. But in reality, the delivery of information is not done online, but with current information such as the delivery of information is done in an intermediary between lecturers and students, which must be done face to face so get a piece of information. So in that event, a system is needed to be able to convey information with a Web-based system so that delivery can be done online and can be accessed anytime and anywhere without being limited by time and space. In this study, using the literature review research method as a comparison material on existing research.